A Genome-Wide Association Study Reveals New Loci for Resistance to Clubroot Disease in Brassica napus - Li, Lixia; Luo, Yujie; Chen, Biyun; Xu, Kun; Zhang, Fugui; Li, Hao; Huang, Qian; Xiao, Xin; Zhang, Tianyao; Hu, Jihong; Li, Feng; Wu, Xiaoming (Frontiers in Plant Science, 2016)
Rapeseed (Brassica napus L.) is one of the most important oil crops in the world. However, the yield and quality of rapeseed were largely decreased by clubroot (Plasmodiophora brassicae Woronin). Therefore, it is of great importance for screening more resistant germplasms or genes and improving the resistance to P. brassicae in rapeseed breeding. In this study, a massive resistant identification for a natural global population was conducted in two environments with race/pathotype 4 of P. brassicae which was the most predominant in China, and a wide range of phenotypic variation was found in the population. In addition, a genome-wide association study of 472 accessions for clubroot resistance (CR) was performed with 60K Brassica Inﬁnium SNP arrays for the first time. In total, 9 QTLs were detected, 7 of which were novel through integrative analysis. Furthermore, additive effects in genetic control of CR in rapeseed among the above loci were found. By bioinformatic analyses, the candidate genes of these loci were predicted, which indicated that TIR-NBS gene family might play an important role in CR. It is believable that the results presented in our study could provide valuable information for understanding the genetic mechanism and molecular regulation of CR.